2005
DOI: 10.1364/opex.13.007631
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dynamic aberrations of the human tear film

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Abstract: The dynamic aberrations introduced by the human tear film are studied by measuring the topography of the tear film surface on 14 subjects using a curvature sensing setup. The RMS wavefront error variation of the data obtained is presented showing the non-negligible contribution of the tear film to overall eye aberrations. The tear film wavefronts are decomposed in their constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…The blink interval used in this study has been reported to be close to that of patients with dry eye during activities in which patients gaze, such as while working on a video display terminal or while reading. [26][27][28][29] A uniform blink interval was used during consecutive measurements to facilitate statistical analysis. Wave front aberrations were measured and recorded at 4 frames per second, whereas OCT images of lower tear meniscus were recorded simultaneously at 2 frames per second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The blink interval used in this study has been reported to be close to that of patients with dry eye during activities in which patients gaze, such as while working on a video display terminal or while reading. [26][27][28][29] A uniform blink interval was used during consecutive measurements to facilitate statistical analysis. Wave front aberrations were measured and recorded at 4 frames per second, whereas OCT images of lower tear meniscus were recorded simultaneously at 2 frames per second.…”
Section: Methodsmentioning
confidence: 99%
“…19 Previous studies 19,29 reported that the Zernike polynomialbased reconstruction algorithm may not fully represent the high spatial frequency changes in wave front aberrations caused by tear film breakup. The root-mean-square (RMS) values from the residual wave front were computed 12 as the square root of the variance of the residual wave front.…”
Section: Wave Front Sensor Data Analysismentioning
confidence: 99%
“…Several studies have been devoted to understanding the dynamics of ocular aberrations, as well as their origin. Fixational eye movements [6,7], tear film dynamics [8][9][10] and micro-fluctuations of accommodation [11,12] were identified as important sources of temporal variation of ocular aberration. However, the relative contribution of each of these elements remains unknown or incompletely known, especially concerning fixational eye movements, i.e.continuous and involuntary movements while the subject is looking at a fixation target.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the trajectories of aberrations measured by HS WFSs suggested that different optical modes exhibit complex temporal behavior, hinting at a combination of diverse underlying mechanisms [11,12]. Another experiment showed the non-negligible contribution of the tear film [13]. However, a number of authors noted that eye motion played a major role, see, e.g., [14,15].…”
Section: Introductionmentioning
confidence: 99%